Scribal education in the Sargonic period - Kraus, Nicholas ca. 20./21. Jh. (Boston BRILL, 2020)
Intro -- Contents -- Acknowledgments -- Abbreviations -- Illustrations -- Chapter 1 Introduction -- 1.1 The Sargonic Period -- 1.2 Previous Research -- 1.3 The Concept of a Curriculum -- 1.4 The Sources -- 1.4.1 Typology -- 1.4.1.1 Type I/P: Prisms and Large Multicolumn Tablets -- 1.4.1.2 Type II: Teacher-Student Exercises -- 1.4.1.3 Type III: Single- and Two-Column Tablets -- 1.4.1.4 Type IV: Lentils -- 1.4.1.5 Plans and Drawings -- 1.4.1.6 Unclassified -- 1.4.1.7 Typological Distribution -- Chapter 2 Writing Technology and Paleography -- 2.1 Tablet Manufacture -- 2.2 The Stylus -- 2.3 Tablet Layout and Organization -- 2.4 Current Research on Sargonic Paleography -- 2.5 Typology of Sargonic Tablets -- 2.5.1 Early Sargonic -- 2.5.2 Middle Sargonic -- 2.5.3 Classical Sargonic -- 2.5.4 Diagnostic Signs -- 2.6 Contextualizing Paleographic Developments -- 2.7 Tablet Orientation -- 2.8 Summary and Conclusion -- Chapter 3 The School Texts -- 3.1 Introduction -- 3.2 Elementary Exercises -- 3.2.1 Sign Practice -- 3.2.1.1 Sign Lists -- 3.2.1.2 Repetitive Practice and Doodles -- 3.2.1.3 Syllable Alphabet A -- 3.2.2 Drawing -- 3.2.3 Thematic Lists -- 3.2.3.1 The KA/SAG List -- 3.2.3.2 Personal Name Lists -- 3.2.3.2.1 NIN List -- 3.2.3.2.2 Mixed Names -- 3.2.3.2.3 The LU₂ List -- 3.2.3.2.4 The Ur Lists -- 3.2.3.2.5 Theophoric Element List -- 3.2.3.2.6 Akkadian Name Lists -- 3.2.3.3 Lists of Realia -- 3.2.3.3.1 Wood and Metal Objects -- 3.2.3.3.2 Aromatic Lists -- 3.2.3.4 Mixed Thematic Lists -- 3.2.3.5 Lists of Divine Names -- 3.2.3.6 Lists of Geographic Names -- 3.2.4 Conclusions -- 3.3 Mathematics and Metrology -- 3.3.1 Introduction -- 3.3.2 Geometric Problems -- 3.3.3 Geometric Designs -- 3.3.4 Mathematical Miscellanea -- 3.3.5 Land Survey -- 3.3.6 Ground Plans and Maps -- 3.3.7 Conclusion -- 3.4 Model Administration -- 3.4.1 Introduction.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Hochschulschrift